Planning and Policy on Children's Literature in Indonesia - Encik Savira Isnah; Sujinah Sujinah; Anas Ahmadi; Mintowati Mintowati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Studies on the planning and policy of children's literature are still rarely found in scientific papers. This is because the process of forming a literary policy is a process that is not easy. After all, it is associated with various matters and layers of needs. On the other hand, literary planning and policy are usually included in the language education policy, not having its land. Today, children's literature has become a means of education and communication to children throughout the world. Children's literature is also an essential part of the delivery of language (mother, national, and foreign) and ideology to children. The love of children's literature has only use as a business area for the book industry without a full review of content. Thus, the policy and planning on children's literature become vital, given the children of the next generation of language, culture, and nation.